The Textual Background of the Gospel of Matthew in Ge‘ez - Zuurmond, Rochus (Aethiopica, 2001)
The Gospel of Matthew in Ge‘ez has been handed down in two ancient Versions: A-text and B-text. The A-text is the earlier one, translated from the Greek and completed not later than the 6th century. It is a very ‘free’ translation, adapting the text not only to a Semitic vernacular but also to a new cultural background. The Vorlage of the A-text was rather close to the Byzantine type of text, but it has more readings in common with Greek manuscripts such as ﬡ, W and B, than those commonly understood as ‘Byzantine.’ The B-text, although strongly influenced by the A-text, removes practically all translational liberties of the A-text. It contains readings that seem to have originated from Syriac or Coptic Gospels and therefore is probably a medieval revision of the A-text on the basis of Arabic Gospels. Existing European editions of the Gospel of Matthew by and large exhibit a B-text.